Pengaruh Social Media Marketing dan Store Location Terhadap Peningkatan Buying Interest Masyarakat di Pizza Jaber - Muhamad Uwes (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This research was conducted to determine the effect of social media marketing and store location on increasing people's buying interest in Pizza Jaber. Survey data was collected by distributing questionnaires to respondents, especially those in the South Surabaya area who did not know about Pizza Jaber. Sampling was carried out using a purposive sampling method. Questionnaires will be distributed to the public and 97 questionnaires will be used as material for research analysis. This research uses PASW Statistics 18 SPSS. This study examines the effect of social media marketing and store location on increased buying interest. It was found that social media marketing had a significant effect on increasing buying interest. In addition, store location has a significant effect on increasing buying interest.